Pengembangan Sistem Informasi Inventory Obat berbasis Web pada Puskesmas Klagenserut - Ajirizky Priagus Sunutama Ashshidiq; Satrio Agung Wicaksono; Djoko Pramono (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
The Klagenserut Public Health Center is one of the main health centers in the Jiwan District. As the main health center, the Klagenserut Community Health Center is a place for supplying drugs and distributing drugs to the villages in which they work. There is a pharmacist division in charge of managing and distributing drugs. However, in doing so, pharmacists still use the manual method, namely recording inventory data and drug distribution manually. This method causes difficulties in checking drug data and drug stocks. Based on the description of the problem, there is a solution, namely making a web-based drug supply information system. The features contained in the system can perform data storage, drug stock information, print drug stock reports on a monthly basis and search drug data. The drug inventory information system was developed through the stages of the Waterfall method. The development process is carried out based on 4 stages. Starting from the stage of system requirements analysis, system design, system implementation and the last stage is system testing. In the last stage, testing was carried out with 2 methods, the first was black-box testing and the second was user acceptance testing. Based on the results of the system test using these 2 methods, the information system created has been in accordance with user needs.